Growth-promoting function of the cGAS-STING pathway in triple-negative breast cancer cells - Liu, Liang-Chih; Shen, Yi-Chun; Wang, Yuan-Liang; Wu, Wan-Rong; Chang, Ling-Chu; Chen, Ya-Huey; Lee, Chuan-Chun; Wang, Shao-Chun (Frontiers in Oncology, 2022)
The cGAS-STING axis is one of the key mechanisms guarding cells from pathogen invasion in the cytoplasmic compartment. Sensing of foreign DNA in the cytosol by the cGAS-STING axis triggers a stress cascade, culminating at stimulation of the protein kinase TBK1 and subsequently activation of inflammatory response. In cancer cells, aberrant metabolism of the genomic DNA induced by the hostile milieu of tumor microenvironment or stresses brought about by cancer therapeutics are the major causes of the presence of nuclear DNA in the cytosol, which subsequently triggers a stress response. However, how the advanced tumors perceive and tolerate the potentially detrimental effects of cytosolic DNA remains unclear. Here we show that growth limitation by serum starvation activated the cGAS-STING pathway in breast cancer cells, and inhibition of cGAS-STING resulted in cell death through an autophagy-dependent mechanism. These results suggest that, instead of being subject to growth inhibition, tumors exploit the cGAS-STING axis and turn it to a survival advantage in the stressful microenvironment, providing a new therapeutic opportunity against advanced cancer. Concomitant inhibition of the cGAS-STING axis and growth factor signaling mediated by the epidermal growth factor receptor (EGFR) synergistically suppressed the development of tumor organoids derived from primary tumor tissues of triple-negative breast cancer (TNBC). The current study unveils an unexpected function of the cGAS-STING axis in promoting cancer cell survival and the potential of developing the stress-responding pathway as a therapeutic target, meanwhile highlights the substantial concerns of enhancing the pathway’s activity as a means of anti-cancer treatment.